Report of the IOC Evaluation Commission for the Games of the XXX Olympiad in 2012 (IOC, 2005)
The International Olympic Committee (IOC) today released the report prepared by the Evaluation Commission following its visits to the five Candidate Cities to host the Games of the XXX Olympiad in 2012 - Paris, New York, Moscow, London and Madrid(1).